2014
DOI: 10.1088/0953-8984/26/25/256003
|View full text |Cite
|
Sign up to set email alerts
|

Strain tuning of magnetism in Mn doped MoS2 monolayer

Abstract: We study the strain tuning of magnetism in Mn doped MoS2 monolayer system. With the increase of the tensile strain, the magnetic ground state changes from a state with total magnetic moment Mtot =1.0 B to another state with Mtot =3.0 B for single doping in a 4 × 4 supercell. Physical mechanism is elucidated from the effects of the local bonding and geometry symmetries on orbital hybridization. In addition, we find the ferromagnetic coupling is favored for small distances between Mn atoms corresponding to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Theoretical studies have shown that local magnetism can be introduced in semiconducting MoS 2 via substitutional doping with magnetic elements, such as V, Cr, Mn, Fe, Co, or Ni. [17][18][19][20] The changes in the electronic and magnetic structures upon doping can subsequently affect the valley pseudospin. However, incorporating these magnetic dopants into monolayer MoS 2 lat tice in a controllable manner remains challenging [21][22][23] and has hindered the systematic study of their influence on the valley pseudospin.…”
mentioning
confidence: 99%
“…Theoretical studies have shown that local magnetism can be introduced in semiconducting MoS 2 via substitutional doping with magnetic elements, such as V, Cr, Mn, Fe, Co, or Ni. [17][18][19][20] The changes in the electronic and magnetic structures upon doping can subsequently affect the valley pseudospin. However, incorporating these magnetic dopants into monolayer MoS 2 lat tice in a controllable manner remains challenging [21][22][23] and has hindered the systematic study of their influence on the valley pseudospin.…”
mentioning
confidence: 99%
“…In addition, defect-free MoS 2 monolayer and MoS 2 monolayer in the presence of single S-vacancy as well as single Mo-vacancy do not exhibit any magnetic properties [9]. However, magnetism is found in the MoS 2 monolayer when the monolayer is doped by some transition metal atoms [10] and nonmagnetic elements [11], in which the induced local magnetism can be controlled via geometrical distortions [12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of intrinsic defects have been found to form local moments [27][28][29][30][31] in MX 2 materials and suggestions have been made to make the MX 2 materials magnetic by adsorption of impurity atoms, 27,28,32,33 or by substituting M or X atoms with impurity atoms. 28,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Even though the Mermin-Wagner theorem 7,8 tells us that there is no long range ordering in two dimensions for isotropic Heisenberg exchange, few attempts have been made to determine the exchange coupling between magnetic impurities 33,37,38,40,41,47,51 and it was only very recently that the magnetic anistropy of a defect was calculated, for an antisite defect in MoS 2 . 31 Replacing some of the M atoms with Hund's-rule coupled transition metal atoms like Mn or Fe gives rise to deep impurity levels in the semiconductor gap.…”
Section: Introductionmentioning
confidence: 99%
“…Where attempts have been made to estimate the Curie temperature, the predicted values are either very low or the concentration of transition metal dopant is so high that the doped material is no longer a semiconductor. 35,37,38,40,41,50 Based upon the electronic structure shown in Fig. 1(b), we explore a different approach to making MoS 2 ferromagnetic in this manuscript.…”
Section: Introductionmentioning
confidence: 99%